Packing chromatic number of certain fan and wheel related graphs - S. Roy (AKCE International Journal of Graphs and Combinatorics, 2017)
The packing chromatic number of a graph is the smallest integer for which there exists a mapping such that any two vertices of color are at distance at least . In this paper, we compute the packing chromatic number for certain fan and wheel related graphs.